How to Avoid the Transformation of Barriers to OSS Adoption in Public Administration into Barriers for Regional Development - Van Leeuwen, Manon; Velkova, Julia; Ozel, Buelent (Ios Press, 2006)
Despite the fact that public sector's interest in open source is intensifying, as many governments turn to freely available software in the belief that it is quick and inexpensive to implement, and that it can be tailored to their needs, Open Source Software (OSS) still faces barriers. In many regions of Europe, that include mostly Associate Candidate Countries (ACC) and New Member States (NMS), the barriers are even more pronounced, because of various social, political, economical, and technical factors. This paper will dive into the barriers and obstacles faced, and will refer to successful experiences that provide important lessons learned for the take-up of OSS in Public Administration. Governments are in the unique position of pushing the adoption of open source. The large-scale adoption of vertical applications at the local level and the influence of favorable procurement will come together to make OSS government application a viable option during the next five years.